Contract management of municipal public services: the Slovak experience - Mikušová Meričková, Beáta; Nemec, Juraj; Jakuš Muthová, Nikoleta (SPRINGERNATURE, 2024)
Contracting out services in the public sector should convey efficiency gains compared to the in-house delivery of these services because of the competition element. However, results from practice do not confirm this assumption. Generalising the reasons for this situation is still problematic, but there is no doubt that the quality of managing the processes of contracting out of public services should be the factor. The aim of this paper is to contribute to the discussion on contract management in the public sector by analysing the quality of contract management in Slovak municipalities in the context of contracting out risks as defined by the principal-agent theory. The study uses own methodological approach for quantifying the determinants of the quality of contract management in relation to the contracting out risks using Saaty's expert method. In total, 7 variables were constructed, and 3416 contracts are evaluated. Similarly to most existing studies, the results indicate severe problems in the quality of contract management in municipal sector, which increase the risks associated with contracting out. The most prevalent reserves in the quality of contract management of contracted local public and ancillary services in the Slovak municipal conditions are related to the selection of the public procurement procedure; the irregular monitoring of the quality of external production; and the type of payment. The outcomes clearly show that potential increases in efficiency via contracting out are unequivocally limited by the low quality of contract management.
Smluvní řízení obecních veřejných služeb: zkušenost Slovenska
Keywords: performance-measurement; accountability; czech; privatization; cooperation; competition; collection; reverse; state; měření výkonnosti; odpovědnost; český; privatizace; spolupráce; konkurence; sběr; zpětný; stát